Northwoods fish cookery - Berg, Ron, 1942- (University of Minnesota Press, 2000)
A fishing guide and avid fisherman as well as an accomplished chef, Ron Berg brings together his love of the outdoors and passion for food in Northwoods Fish Cookery. The book includes Berg's own fishing tips, humorous anecdotes, and lore from the Gunflint Trail, giving the book a crisp, northwoods flavor sure to delight outdoor enthusiasts and lovers of fine food everywhere.